Փիլիսոփայությունը Համո Սահյանի պոեզիայում - Սառաջյան, Զարինե («Դիզակ պլյուս» հրատարակչություն)
Статья посвяще на литературной интерпретации стихотворений Амо Сагяна на уровне философии. Суть философии А. Сагяна заключается в исследовании человеческой души. Природа для А. Сагяна-это на чало самопознания и миропознания. The article is devoted to the literary interpretation of Hamo Sahyan’s poems on the level of philosophy. The core of Sahyan’s philosophy is a human soul’s learning. The nature for Sahyan is a start of self-identification and world understanding.
Keywords: Գրականություն; Փիլիսոփայություն